POLA PARTISIPASI MASYARAKAT LOKAL DALAM PENGEMBANGAN WISATA TIRTO TANI DJOJO DI DESA TIRU LOR, KEC. GURAH, KAB. KEDIRI - A Zahid; Afra Zahrotul Ummah (Jurnal Abdi Masyarakat (JAM), 2021)
Tirto Tani Djojo Tourism is one of the new tourist destinations in the Gurah District, Kediri Regency. Basically, this tour is managed by a group called the "kelompok sadar wisata", this group moves to generate a community-based economy. Starting from the grassroots that aims to arouse the fury of the surrounding community, the main mission is the revival of the local community's economy. However, the existence of a tourism awareness group that plays an active role in the development of tourism, is able to arouse the enthusiasm of other communities, so that the pattern of community participation in the development of Tirto Tani tourism runs optimally. The method used in this research is the empowerment model that starts with the stages, planning, implementation, and supervision. The results of this study are, the pattern of community participation in the development of tourist destinations Tirto Tani Djojo, not only has an impact on the surrounding communities, but also the community also gets satisfaction in the form of utilizing vacant land, building social solidarity in tourism development, and Tiru Lor village is becoming known. by the community.